Dekret Prezydenta Rzeczypospolitej Polskiej o odpowiedzialności karnej za zbrodnie wojenne z dnia 30 marca 1943 roku - Uczkiewicz, Dominika (Wydawnictwo Uniwersytetu Wrocławskiego, 2019)
On 30 March 1943 the Decree of the President of the Polish Republic on Criminal Liability for War Crimes, the first normative act setting down the legal basis for persecution of war criminals issued by one of the Allies during the Second World War, was proclaimed. The promulgation of the decree can be considered as the turning point in the Polish government-in-exile’s policy towards the problem of the prosecution and punishment of Nazi criminals, which started in autumn 1939. After the announcement of the draft decree, developed by the Polish minister of justice, professor of state law, Wacław Komarnicki and by an international lawyer, professor of criminal law, Stefan Glaser in the spring of 1942, a fierce discussion on the legal act’s concept broke out in the Polish government and lasted until November 1942. Although all Polish politicians agreed on the need to define the principles of individual criminal liability for war crimes, the proposal to promulgate criminal legislation with retroactive effect aroused much controversy. However, as the course of these debates shows, the critical point was not the mere fact of violating the lex retro non agit principle. The scepticism of some Polish politicians towards this idea resulted from purely pragmatic reasons and was caused by lack of support from the American and British governments for the proposal to define legal frames for the future trials of war criminals (this attitude changed only in spring 1945). This article presents the genesis and provisions of the Decree of the President of the Polish Republic on Criminal Liability for War Crimes of 30 March 1943 in the context of international debates on international criminal law and individual liability for war crimes. It argues that the legislative works on the decree and its proclamation in March 1943 mark an important point in the process of shaping the concept of prosecution and punishment of war criminals during the Second World War.
Keywords: war crimes; Second World War; Polish government in exile; individual liability for war crimes; Komarnicki Wacław